The 3-Second Rule in Hereditary Pure Cerebellar Ataxia: A Synchronized Tapping Study - Matsuda, Shunichi (PLoS One, 2015)
The ‘3-second rule’ has been proposed based on miscellaneous observations that a time period of around 3 seconds constitutes the fundamental unit of time related to the neuro-cognitive machinery in normal humans. The aim of paper was to investigate the temporal processing in patients with spinocerebellar ataxia type 6 (SCA6) and SCA31, pure cerebellar types of spinocerebellar degeneration, using a synchronized tapping task. Seventeen SCA patients (11 SCA6, 6 SCA31) and 17 normal age-matched volunteers participated. The task required subjects to tap a keyboard in synchrony with sequences of auditory stimuli presented at fixed interstimulus intervals (ISIs) between 200 and 4800 ms. In this task, the subjects required non-motor components to estimate the time of forthcoming tone in addition to motor components to tap. Normal subjects synchronized their taps to the presented tones at shorter ISIs, whereas as the ISI became longer, the normal subjects displayed greater latency between the tone and the tapping (transition zone). After the transition zone, normal subjects pressed the button delayed relative to the tone. On the other hand, SCA patients could not synchronize their tapping with the tone even at shorter ISIs, although they pressed the button delayed relative to the tone earlier than normal subjects did. The earliest time of delayed tapping appearance after the transition zone was 4800 ms in normal subjects but 1800 ms in SCA patients. The span of temporal integration in SCA patients is shortened compared to that in normal subjects. This could represent non-motor cerebellar dysfunction in SCA patients.